Different network typologies in patenting activity of academic inventors through time: the case of Italian chemists in the period 2000–2011 - Saveria Capellari; Domenico De Stefano (Triple Helix, 2016)
In this paper, we present the results of a network analysis applied to academic patent data in a subsector of the chemical field in Italy in the period 2000-2011. In particular, we analyse the micro-level interactions to point out the different network structures shaped by university-owned and university-invented patents. We detected three subnetwork typologies (labelled type A, B, and C) that exemplify different qualitative relational structures as well as different attributions to propriety rights. Type A (open science) exemplifies the typical owned patent; type B (multiple ties) represents the hybrid structure with multiple ties and involvement of academics as individuals and of universities as organisation; type C (disconnected subnetworks) represents the typical invented patent with no role of universities as organisation. The whole network seems to show a breaking point in terms of connectivity around 2005, a year that marks a change in policy rule and strategic orientation of Italian universities towards patenting. After 2005, the number of actors grew disproportionally and the network appears disconnected in several comparable components. Also, the composition in terms of subnetwork types changed. The overall picture seems to underline a big structural change dominated by the important increase of academic patenting both direct (university ownership) and indirect (increasing academic patenting).
Keywords: 330; Social network analysis; Academic patenting; Co-invention networks; Network components; Science-industry linkages